The Year in Review for Renal Cancer (Journal of Kidney Cancer, 2020)
The treatment of kidney cancer has made some remarkable strides over the last few years. Two regimens received Food and Drug Administration (FDA) approval, multiple biomarkers were reported to show promise, and further enhancement and refinement of the prognostic characteristics occurred. The combinations of anti-angiogenic tyrosine kinase inhibitors with immune checkpoint inhibitors have rapidly become the preferred therapies in the front-line setting of advanced renal cancer.